IMPLEMENTASI PENGGUNAAN KEMAMPUAN COMPUTATIONAL THINKING PADA SEKOLAH ANAK-ANAK: ANALISIS BIBLIOMETRIK (2014-2024) - Zafrullah Zafrullah; Resky Nuralisa Gunawan; Haidir Haidir; Atika Miftah Ramadhani (Jurnal Binagogik, 2024)
This research aims to analyze research trends regarding the Use of Computational Thinking Skills in Children's Schools. Using predetermined keywords, researchers analyzed 124 documents in the Scopus Database using the R program and VOSviewer. From the results of the analysis that has been carried out, it can be concluded that research regarding the implementation of Computational Thinking skills in children's schools in the Scopus database began in 2014 to 2024, with peak publications and citations occurring in 2022 with 22(17.74%) documents, 21( 23.59%) documents have been cited, 282(11.41%) the number of citations, and the h-index is 9. China is the most produComputational Thinkingive country with 24(19%) documents and 295(11.94%) citations. The Education University of Hong Kong was a produComputational Thinkingive affiliate with 11(8.87%) documents. Siu-Cheung Kong from The Education University of Hong Kong is the most produComputational Thinkingive writer with an h-index of 4. The journal "Computers and Education" is ranked highest with an h-index of 6. Bers et al. (2014) is the document with the highest citations with 609(24.66%) total citations. There are 40 keywords divided into 5 clusters, with the keywords "Gender" and "Primary Education" being the recommended keywords for conduComputational Thinkinging further research in the field of Implementing Computational Thinking in children's schools.